REHABILITATION OF REPRODUCTIVE FUNCTION IN YOUNG ONCOLOGIC PATIENTS AFTER THE ORGAN-SPARING TREATMENT (BRIEF COMMUNICATION) - E. A. Chulkova (IRBIS LLC, 2016)
Nowadays, during rehabilitation of oncologic patients of fertile age, one of the main tasks is the restoration and maintenance of menstrual function after radical treatment to recover patients fertility. The main issue faced by obstetricians and gynecologists during management of pregnancy in patients who had undergone invasive treatment of pre malignancy and early cervical cancer, is the threat of prematurity and premature labor. There is no unanimous opinion about tactics of labor management in such females. In order to recover normal ovulatory menstrual cycles the application of combined hormonal contraceptives (CHC) for 6 months is indicated.